Structural Approach of Miss Peregrine’s Home for Peculiar Children Through Fantastic Theory - Khairunnisa, Nurul Izzah; Setyabudi, Titis (Journal of Language and Literature Studies, 2025)
This study investigates the fantastic elements in Miss Peregrine’s Home for Peculiar Children through a structural analysis grounded in Tzvetan Todorov’s Fantastic Theory. The film was chosen because of its rich and complex depiction of a supernatural world that remains embedded within a coherent and believable narrative framework. Adopting a qualitative descriptive method, the research examines how motifs, plot structures, characters, settings, and decor work together to construct the fantastic dimension of the story. Data were obtained primarily through close observation of selected film scenes, with additional insights drawn from relevant secondary literature to strengthen interpretation. The analysis demonstrates that the film skillfully blends both marvelous and uncanny elements, such as recurring time loops, peculiar abilities possessed by children, and the presence of mythical creatures, in order to sustain the logic of its fantasy world. These elements function not merely as imaginative spectacle but as integral narrative devices that support broader thematic concerns. Central to these are issues of identity formation, the protective boundaries of community, and the tension between freedom and safety, which resonate with universal human dilemmas. The findings suggest that Todorov’s theoretical framework is particularly effective for dissecting the layered structures of fantasy in contemporary cinema, as it highlights the interplay between realistic and supernatural elements that define the genre. In conclusion, the study affirms that fantasy in film is not solely a mode of escapism but also a medium for deeper reflection on social, psychological, and existential aspects of human experience.